A new genus of Silvaninae (Coleoptera: Silvanidae) with two new species from the Malay Peninsula - Yoshida, T.; Hirowatari, T.; Hashim, Rosli (Magnolia Press, 2017)
A new silvanid genus Dentirotacorimus gen. nov. is described based on specimens collected from Ulu Gombak (Malay Peninsula), Malaysia. Two new species, D. reticulatus sp. nov. and D. zigzag sp. nov., are described herein. A key to species of this genus and a table listing states of diagnostic characters of Corimus-like genera, including this new genus, are provided.